Diagnostic Implications of Irritable Bowel Syndrome Is an Independent Risk Factor for Undergoing Surgical Interventions in Patients with Inflammatory Bowel Disease - Yuhan Fu; Nisheet Waghray; Ronnie Fass; Gengqing Song (Diagnostics, 2023)
Background: Inflammatory bowel disease (IBD) and irritable bowel syndrome (IBS) can present with overlapping symptoms, making diagnosis and management challenging. Patients with IBD in remission may continue to experience IBS symptoms. Patients with IBS were found to have a disproportionately higher prevalence of abdominal and pelvic surgeries than the general population. Aims: The aim of this study was to determine whether IBS is a risk factor for undergoing surgical interventions in patients with IBD and explore the diagnostic implications of these findings. Methods: A population-based cohort analysis was performed using TriNetX. Patients with Crohn’s disease + IBS (CD + IBS) and ulcerative colitis + IBS (UC + IBS) were identified. The control groups consisted of patients with CD or UC alone without IBS. The main outcome was to compare the risks of undergoing surgical interventions between the cohorts. The secondary outcomes were to compare the risks of developing gastrointestinal symptoms and IBD-related complications between the cohorts. Results: Patients with IBD who subsequently developed IBS were more likely to experience gastrointestinal symptoms than those without IBS (p < 0.0001). Patients with concomitant IBD and IBS were more likely to develop IBD-related complications, including perforation of the intestine, gastrointestinal bleeding, colon cancer, and abdominal abscess (p < 0.05). Patients with concomitant IBD and IBS were more likely to undergo surgical interventions than patients without IBS, including colectomy, appendectomy, cholecystectomy, exploratory laparotomy, and hysterectomy (p < 0.05). Conclusions: IBS appears to be an independent risk factor for patients with IBD to develop IBD-related complications and undergo surgical interventions. Patients with concomitant IBD and IBS could represent a unique subgroup of IBD patients with more severe symptoms, highlighting the importance of accurate diagnosis and management in this population.